Analisis Swot dalam Perspektif Al-Qur’an - Al Masithoh, Silvinatin (CBJIS: Cross-Border Journal of Islamic Studies, 2023)
The aim of this research is that the Al-Qur'an is a holy book that contains various solutions to all problems in life. Thousands of verses in it can be used as a guide to life, in accordance with the name of the Al-Quran, namely "al-Huda" which means guidance. Guidelines for humans in dealing with various kinds of problems in everyday life. Sticking to the Koran can keep people away from feelings of despair and distress. In order for humans to be able to control themselves, it is appropriate for us to be able to understand the contents and contents of the verses of the Koran by studying them. By using the maudlu'I method, namely understanding the Al-Qur'an based on a theme. This can make it easier to connect the verses of the Koran with everyday life. The type of research used is library research, where the data is mostly sourced from literature, books and scientific works related to the theme. Based on the research results, it can be concluded that humans have four components inherent in them. Namely strengths, weaknesses, exploiting opportunities and awareness of threats. If humans are aware and can control the four components above, then they will live this life well.